Evaluating the cytotoxic activity of lactobacillus plantarum IIA-1A5 against MCF-7 human breast cancer cells and identifying its surface layer protein gene - Adiyoga, Reza; Budiman, Cahyo; Abidin, Zaenal; Fujiyama, Kazuhito; Arief, Irma Isnafia (Penerbit Universiti Kebangsaan Malaysia, 2024)
Breast cancer is a serious global health concern, with a high mortality rate worldwide. Using natural compounds as potential cancer therapies is a promising approach to address this issue. Previous research has shown that probiotic lactic acid bacteria (LAB) and their metabolites, such as surface layer protein (slp), have a positive impact on a variety of health disorders, including cancer. The purpose of this study was to evaluate the ability of Lactobacillus plantarum IIA-1A5 to suppress the growth of the MCF-7 breast cancer cell line and detect the presence of the slp gene. Intracellular and extracellular protein fractions were isolated from L. plantarum IIA-1A5 cultures. The protein concentrations and molecular weights of the extracts were measured. The anticancer activity of the extracts was assessed using the MTT cytotoxicity test, and IC50 values were calculated. The slp gene was identified through polymerase chain reaction (PCR) amplification and nucleotide sequencing. The results demonstrated that L. plantarum IIA-1A5 had a concentration-dependent inhibitory effect on MCF-7 breast cancer cells, with IC50 values of 6.831 and 12.35 μg/mL for intracellular extracts and extracellular extracts, respectively. Additionally, PCR amplification and nucleotide sequencing confirmed the presence of the slp gene, which may contribute to the strain’s anticancer abilities. These findings suggest the potential of L. plantarum IIA-1A5 as a natural anticancer agent against MCF-7 breast cancer cells. Further research is warranted to elucidate the underlying mechanisms of L. plantarum IIA-1A5 in breast cancer treatment.